Development of Interactive Learning Media Helped Kine Master on Themes of Objects, Animals, and Plants Around Me Class 1 SD - Asrida Ramadhani; Dinda Yarshal (PT Inovasi Pratama Internasional, 2023)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character and the skills needed by themselves and society. This type of research uses development research methods. or Research and Development (R&D). Research methods are used to produce certain products and test the effectiveness of these products. This research is intended to develop interactive learning media assisted by Kine Master with modifications to the design of the ADDIE model development which consists of several stages including analysis, design, development, implementation and evaluation. From the results of the needs analysis, namely researchers looking for solutions by developing products in the form of interactive learning videos with the help of Kine Master Themes Objects, Animals and Plants Around Me Class 1 SD which can facilitate teachers and students in the learning process. The results of the curriculum analysis can be described as follows: The 2018 revision of the 2013 curriculum has been used at PELITA Vocational Schools and the learning objectives in the media are described from learning indicators, because not all material can be conveyed through interactive learning. Kine Master-assisted media, it is necessary to select learning materials that are guided by the Core Competencies and Basic Competencies of Grade 1 Elementary School semester. Based on the results of research and development that has been carried out by researchers it can be concluded that research and development uses stages with the ADDIE model which is modified into 3 stages, namely : analysis, design, and development have resulted in a product in the form of interactive learning media videos assisted by Kine Master on the themes of objects, animals and plants around me.